Morpho-molecular characterization and formaldehyde resistance of a fungus isolated in an anatomy laboratory (Research, Society and Development, 2025)
Fungi are eukaryotic beings, with cellular organization and DNA delimited by a nuclear envelope. Morphologically, they appear as yeasts, filamentous, called molds, being microscopic or macroscopic. Climatic conditions such as in the Amazon favor closed environments with high humidity, factors that enhance the development phase of these microorganisms and increase their ability to propagate, making them highly adaptive contaminants. This study aimed to morph-molecularly characterize and evaluate the formaldehyde resistance capacity of the fungus isolated in an anatomy laboratory. It was obtained from the liquid formaldehyde suspension of the tanks with anatomical parts. Morphologically analyzed through the macro and microscopic, and subjected to the process of DNA extraction for sequencing and identification. Resistance tests were also carried out in formalin concentrations and growth capacity at temperatures of 37ºC, 45ºC and 50ºC, as well as detection of the enzymatic activity of proteases. As a result, the studied isolate obtained satisfactory growth at all temperatures tested, as well as at all formalin concentrations, with DNA extraction and sequencing the fungus indicated that it was of the Phanerochaete genus. The isolate showed resistance to all concentrations of formaldehyde tested, with emphasis on the concentration used in the laboratory. It grew well at the high temperatures tested, but showed no halo in protease activity. However, it was possible to verify a biotechnological potential, which needs more detailed future studies that indicate it as an alternative in the bioremediation of sediments contaminated with formaldehyde, and to know it better for possible control of its contamination in the collection of anatomical parts of the anatomy laboratory.